2003
DOI: 10.1002/cncr.11514
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord malignant astrocytomas

Abstract: Coupling a heterogeneous catalytic reaction with a membrane separation can solve the problem concerning catalyst separation in situ from the reaction mixture and make the production process continuous. In this article, the feasibility of continuous hydroxylation of phenol to hydroquinone (HQ) and catechol (CA) over ultrafine TS‐1 catalyst in a submerged ceramic membrane reactor system is investigated. It has demonstrated that the submerged ceramic membrane reactor system can maintain a steady production of HQ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 43 publications
3
53
1
Order By: Relevance
“…Results of a statistical analysis of age as a prognostic factor were reported in 15 studies [2,5,24,27,28,30,34,41,46,49,56,59,60,64,65] (Table 4). Of these, 13 were classified as category A, 8 failed to find a significant relationship between age and prognosis [2,24,28,30,34,46,56,59], as did one additional category B study [27].…”
Section: Agementioning
confidence: 99%
See 4 more Smart Citations
“…Results of a statistical analysis of age as a prognostic factor were reported in 15 studies [2,5,24,27,28,30,34,41,46,49,56,59,60,64,65] (Table 4). Of these, 13 were classified as category A, 8 failed to find a significant relationship between age and prognosis [2,24,28,30,34,46,56,59], as did one additional category B study [27].…”
Section: Agementioning
confidence: 99%
“…Contrary to these four reports, the last category A study [49] reported age over 20 to be associated with increased survival. In addition, one category B study dealing exclusively with malignant astrocytomas reported advanced age to decrease median survival [65].…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations